Zeolite Oil Palm Compost-Based Organomineral Fertilizer for Shallot Agronomic Performances and N Substitution - Muhammad Tegar Putra Bahari; Marwanto Marwanto; Fahrurrozi Fahrurrozi; Merakati Handajaningsih (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2022)
Application of organomineral fertilizer (OMF), which is the product of the inclusion of zeolite and palm oil compost in urea needs to be studied to determine its appropriate dose for the growth and yield of shallots and N substitution. This pot experiment was conducted from October to December 2020 at the Teaching and Research Field of Agriculture Faculty and consisted of five treatments arranged in a completely randomized design with five replications. The treatments were (1) 1.0 g urea, (2) 0.5 g urea + 1.15 g OMF, (3) 0.5 g urea + 2.30 g OMF, (4) 0.5 g urea + 3.45 g OMF, and (5) 0.5 g urea + 4.60 g OMF. The results showed that combined application of 0.5 g urea + 4.60 g OMF produced the highest values of plant height (30.60 cm), number of leaves (30.90), fresh weight of tubers per clump (30.90 g), dry tuber weight per clump (24.3 g), and tuber diameter (16.25 mm). The incorporation of zeolite and palm oil compost in urea reduced the application rate of urea up to 50% without reducing the growth and yield of shallot. Thus, N fertilizer use can be enhanced if urea is co-applied with zeolite and palm oil compost.